2007
DOI: 10.1080/00222930701391773
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and taxonomy of intertidal Bryozoa (Cheilostomata) at Akkeshi Bay, Hokkaido, Japan

Abstract: We found 39 cheilostome species among more than 7000 specimens collected at 10 intertidal sites in rocky habitats along the shore of Akkeshi Bay, eastern Hokkaido Island, Japan. These species are herein described in detail and illustrated by scanning electron microscopy. Nine species (23% of total) are described as new (Electra asiatica, Callopora sarae, Conopeum nakanosum, Cauloramphus cryptoarmatus, Cauloramphus multispinosus, Cauloramphus niger, Stomachetosella decorata, Microporella luellae, and Celleporin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Although in the course of this study we directly observed embryos in only two of the species examined (C. spinifer and C. cryptoarmatus), internally brooded embryos have been reported for all the species examined (Dick and Ross, 1988;Dick et al, 2005;Grischenko et al, 2007). These data coupled with our observation of ooecia in the eight species studied strongly suggest that a reduced, maternally produced kenozooidal ooecium and internal brood sac are characters common to all species of Cauloramphus and should thus be appended as diagnostic characters for this genus.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 66%
See 2 more Smart Citations
“…Although in the course of this study we directly observed embryos in only two of the species examined (C. spinifer and C. cryptoarmatus), internally brooded embryos have been reported for all the species examined (Dick and Ross, 1988;Dick et al, 2005;Grischenko et al, 2007). These data coupled with our observation of ooecia in the eight species studied strongly suggest that a reduced, maternally produced kenozooidal ooecium and internal brood sac are characters common to all species of Cauloramphus and should thus be appended as diagnostic characters for this genus.…”
Section: Evolution Of Internal Brooding In Calloporidaesupporting
confidence: 66%
“…Cauloramphus spinifer (Johnston, 1832); Cauloramphus magnus Dick and Ross, 1988; Cauloramphus cryptoarmatus Grischenko, Dick, and Mawatari, 2007; Cauloramphus niger Grischenko, Dick, and Mawatari, 2007; Cauloramphus multispinosus Grischenko, Dick, and Mawatari, 2007. Narrow Strait, Kodiak, Alaska, USA, September-December 1982:…”
Section: Species Examinedmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers with more detailed descriptions (e.g. Dick et al 2005;Grischenko et al 2007) generally include means and standard deviations (but need also to include sample size), in addition to range, so that the data sets can be incorporated into any subsequent analysis (as in this paper). To conform with usual practice, we include ranges in Tables 1, 3 and 4.…”
Section: Methodsmentioning
confidence: 99%
“…The bryozoan was identified as Schizoporella japonica Ortmann (1890) on the basis of the most recent comprehensive redescription of material from Alaska and Japan (Dick et al 2005;Grischenko et al 2007). The original description by Ortmann (1890), as S. unicornis var.…”
Section: Introductionmentioning
confidence: 99%